2022
DOI: 10.1021/acs.jafc.2c05317
|View full text |Cite
|
Sign up to set email alerts
|

T-2 Toxin Caused Mice Testicular Inflammation Injury via ROS-Mediated NLRP3 Inflammasome Activation

Abstract: T-2 toxin treatment causes male reproduction system dysfunction, although the exact mechanism remains unclear. In this research, male Kunming mice and TM4 cells were treated with varying concentrations of the T-2 toxin for evaluating the adverse effect of T-2 toxin on male reproductive function. MCC950 or NAC was used to block NLRP3 inflammasome activation and eliminate reactive oxygen species (ROS) accumulation in the TM4 cell, respectively. The results showed that: (1) T-2 toxin caused testicular atrophy, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…To date, little research has focused on relieving the intestinal toxicity of T-2 toxin. Oxidative stress is the main mechanism underlying T-2 toxin-induced enterotoxicity; hence, alleviating oxidative stress has become a potential means to mitigate/block T-2 toxin-induced intestinal toxicity. , Currently, the main strategy for reducing T-2 toxin enterotoxicity is the use of antioxidant substances or increasing the body’s capacity for antioxidants and lowering oxidative stress. However, the limitations of these strategies include the small number of studies that have investigated T-2 toxin.…”
Section: Advances In Alleviating the Enterotoxicity Of T-2 Toxinmentioning
confidence: 99%
“…To date, little research has focused on relieving the intestinal toxicity of T-2 toxin. Oxidative stress is the main mechanism underlying T-2 toxin-induced enterotoxicity; hence, alleviating oxidative stress has become a potential means to mitigate/block T-2 toxin-induced intestinal toxicity. , Currently, the main strategy for reducing T-2 toxin enterotoxicity is the use of antioxidant substances or increasing the body’s capacity for antioxidants and lowering oxidative stress. However, the limitations of these strategies include the small number of studies that have investigated T-2 toxin.…”
Section: Advances In Alleviating the Enterotoxicity Of T-2 Toxinmentioning
confidence: 99%
“…One important component of innate immunity is the nucleotide-binding oligomerization domain, leucine-rich repeat and pyrin domain containing (NLRP3) inflamma-some (6)(7)(8). It can be activated by various endogenous danger signals, such as cellular perforin (9), extracellular ATP (10), reactive oxygen species (ROS) (11,12), as well as other exogenous factors, leading to its inappropriate activation or mutations that are closely related to RA (13)(14)(15)(16), inflammatory bowel disease (17)(18)(19), gout (20)(21)(22) as well as other inflammatory autoimmune diseases. Clinical studies have confirmed that in RA patients, IL-18, IL-1β, Caspase-1 and NLRP3 were positively expressed in synovial coated cells and subsynovial tissues, especially in the cytoplasm of synovial lined cells, macrophages and a few inflammatory cells within the synovial interstitium.…”
Section: Introductionmentioning
confidence: 99%